QUANTIFICATION OF BIOACTIVE COMPOUNDS IN FREEZE-DRIED FERMENTED BITTER MELON (Momordica charantia L.) EXTRACT USING Lactobacillus fermentum LLB3 - Michael Sean; Sherlina Audrey Marcellino; Lindayani Lindayani; Laksmi Hartajanie (Soegijapranata Catholic University, 2024)
Bitter melon (Momordica charantia L.) is one of the plant-based functional foods, which has many health benefits potential due to its bioactive compounds. The usage of Lactobacillus fermentum LLB3 to ferment bitter melon juice has been studied to increase its functional activities. However, the amount of bioactive compounds contained in the fermented juice have not been studied. Therefore, this research provides the quantification of bioactive compounds, including total phenolic and total flavonoid contained in fermented bitter melon juice. Bitter melon fruit was juiced, filtered, and pasteurized at 80°C for 5 minutes. Fermentation was done by using Lactobacillus fermentum LLB3 with incubation times of 24, 48, and 72 hours. The samples were freeze-dried, and the bioactive components were quantified using the spectrophotometry (UV-Vis) method. All data obtained were analyzed statistically to determine the significance of the difference. Both total phenolic and total flavonoid contents were found to be increased by the pasteurization proses due to the thermal treatment applied. However, the fermentation process did not perform any increase either in total phenolics or total flavonoids. Furthermore, the freeze-drying process did not give a significant effect on flavonoid contents, but higher values of phenolic content were obtained.